ПОЛУПРОВОДНИКОВЫЕ ПРЕОБРАЗОВАТЕЛИ ДЛЯ СВЯЗИ МЕЖДУ АВТОНОМНЫМ ГЕНЕРАТОРОМ И ПРОМЫШЛЕННОЙ СЕТЬЮ - Сокол, Е.И.; Гончаров , Ю.П.; Ересько, А.В.; Замаруев , В.В.; Ивахно, В.В.; Кривошеев , С.Ю.; Родин , Н.Ю.; Маляренко , Е.А.; Лобко , А.В. (Інститут електродинаміки НАН України, Київ, 2012)
The structure of the converter output order of a few kilowatts to connection between the industrial grid 220/380 V and autonomous generator with variable voltage and current parameters are considered. The system of band management, which provides coordination of generator parameters and network with minimum size filter equipment and high noise immunity circuit voltage feedback network are proposed. References 5.